Transported dust modulates aerosol pollution domes over rapidly urbanizing Indian cities - Soumya Satyakanta Sethi; V. Vinoj (Communications Earth & Environment)
Abstract Elevated anthropogenic emissions over cities are said to form distinct pollution domes. Here, we characterize them, exploring their general patterns for 141 Indian cities using satellite-retrieved aerosol optical depth data from 2003 to 2020. We show the existence of a distinct north-south pollution dome pattern across the Indian cities, with the domes for the highly polluted northern cities generally punctured due to regional or long-range transported aerosols, especially dust. Our study highlights the significant role of large-scale circulation and the requirement for synergistic regional and local aerosol pollution mitigation measures for clean air and urban sustainability.